Accounting For Urban Carbon Dioxide: A Review - Zhang, Yan; Li, Juan; Liu, Gengyuan (Journal of Environmental Accounting and Management, 2026)
Cities are the main contributors to the global climate change. Accounting for urban carbon sources and sinks is necessary for the development of low-carbon cities. This paper compares and analyses the carbon accounting standards by summarizing the research of urban carbon accounting items and methods, to serve as a reference for future studies of urban carbon accounting. Three carbon accounting standards are compared to analyse the differences in the applied scales and in the accounting emphasis. Carbon accounting items and methods are conducted based on artificial carbon sources, natural carbon sources and natural carbon sinks. Three suggestions are proposed to further develop urban carbon accounting. First, carbon emissions from human and soil respiration should be included in carbon source accounting. Second, because of the frequent interactions between cities and surrounding areas, the embodied carbon emission of goods and services imported to cities should be emphasized. Third, to increase the accuracy of urban carbon accounting, on site measurement should be reinforced to accumulate first-hand data of time series.